ANALISIS EFEKTIVITAS PELAKSANAAN DANA BANTUAN SOSIAL YANG BERSUMBER DARI ANGGARAN PENDAPATAN DAN BELANJA DAERAH DI KABUPATEN NGADA - Agustina Ngene; Jennie S. Sir; Alfred T. Rantelobo (P3M- Politeknik Negeri Kupang, 2021)
The problem in this research is that it is known that many people are upset and disappointed, because the submission of the proposal does not match the realization in the disposition of Plt. Regent Ngada, even and not comparable to community expectations. The purpose of this research is to find out and explain : 1. As well as what factors influence the implementation of social assistance funds sourced from APBD in Ngada Regency. 2.How the effectiveness of the implementation of social assistance funds sourced from APBD in Ngada Regency.The research method used is descriptive quantitative research methods. The data analysis technique used by researchers is descriptive quantitative analysis. The results showed that the implementation of social assistance funds in Ngada Regency was quite effective and is strongly influenced by various factors including the quality of the apparatus, facilities and infrastructure, as well as supervision from the local government. The conclusion in this study is that the implementation of social assistance funds in Ngada Regency has currently been implemented quite effectively and is influenced by various factors, namely the quality of the apparatus, facilities and infrastructure and supervision. So that in the future the local government of Ngada Regency will be more active in supervising and monitoring the implementation of social assistance funds in terms of absorption or use of budgets as well as administration of social assistance funds